How investor’s behaviour towards investment decision? PLSSEM approach - Ang, Hui Theng; Kong, Kah Weng; Ong, Vnn Nee; Poo, Ling Feng; Tan, Khai Shen (2019)
This research was studied the relationship between individual investment decision making and psychological financial behaviour and Malaysia 14th General Election. The target respondents of this research were included 120 individual investors which involved in the Malaysia stock market with the sampling location at Perak state (Ipoh and Kampar). To execute the five statistics results were Cronbach’s alpha, composite reliability (CR), average variance extracted (AVE), discriminant validity, as well as hypothesis testing. The Partial Least Squares Structural Equation Modeling (PLS-SEM) had been conducted in this research. The results found that there were the significant and insignificant relationship between individual investment decision making and psychological financial behaviour and Malaysia 14th General Election. This research was provided the benefit to the society such as financial investors, investment advisor and financial professional, policymaker and financial market regulator as well as corporate.